Characterization of Au/TiO\(_2\) nanocomposite and its application to photocatalytic degradation of methylene blue - Pham, Minh Thuy; Vu, Chinh Duc; Chu, Thi Thu Hien (Communications in Physics, 2025)
Au nanoparticles were deposited on the surface of TiO2 particles using a photochemical reduction method. This modification creates a surface plasmon effect that enhances the local light intensity at the interface of Au and TiO2 nanoparticles. Au/TiO2 nanocomposites with varying Au content (0.5%, 1%, 3%, and 5%) were synthesized, resulting in Au nanoparticles of approximately 2 nm in size uniformly distributed on the TiO2 surface, forming composite particles of the size ranging from 100 nm to 150 nm. The prepared samples were characterized by infrared spectroscopy (FT-IR), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), UV-Vis absorption spectra, photoluminescence spectra and X-ray photoelectron spectroscopy (XPS). The photocatalytic activity of the nanocomposites was evaluated. Compared with pure TiO2, Au/TiO2 exhibited higher activities for methylene blue decomposition. The rate constants of pseudo-first-order kinetics for Au-modified TiO₂ with Au contents of 0.5%, 1%, 3%, and 5% were 0.0456, 0.0579, 0.0536, and 0.0484 min⁻¹, respectively. These values are 1.66, 2.11, 1.95, and 1.76 times higher than that of unmodified TiO₂.